An innovative multidisciplinary intervention to prevent and treat child obesity: the Epode Umbria Region OBesity Intervention Study (EUROBIS) - Pippi, Roberto; Buratta, Livia (International Multidisciplinary Research Journal, 2020)
The lifestyle’s fundamental role in the approach to the young people with metabolic problems is now supported by the scientific evidence. However, multidisciplinary (including nutritional, physical activity and psychological aspects) intervention studies conducted on this issue are still lacking. This work aims to reflect on issues concerning the EUROBIS multidisciplinary intervention study, which aims to contrast childhood obesity, addressing the complex nutritional, motor, and psychological aspects to improve children’s lifestyle through the implementation of curative and preventive strategies. The curative, clinical approach already proved to be effective in a significant reduction in body weight, BMI, waist circumference, fat mass, waist circumference/height index, and an improvement of Mediterranean diet adherence and physical activity measures, in subjects with overweight/obesity [1]. Now we present the first results of the preventive project "Let’s improve the Umbrian children lifestyle", a school-based intervention, conducted in 2015-16 school year on first classes of primary schools in Umbria (more than 4000 children) resulting in an improvement in Mediterranean diet adherence and physical activity measures. This study confirms that multidisciplinary lifestyle intervention can improve anthropometric, nutritional and physical activity outcomes and represents the cornerstone to build recommendations with a high level of evidence within the Italian standards of care, although it has demonstrate the difficulties of young people and parents to join it.